Evaluation of Adverse Effects of Sodium Stibogluconate in the Treatment of Visceral Leishmaniasis - Miah, Md Abdus Sattar; Salam, Md Abdus; Haque, Md Azizul; Azad, Md Azizul Haque; Haque, Md A K M Enamul; Islam, Quazi Tarikul; Ekram, A R M Saifuddin (KYAMC Journal, 2013)
This descriptive cross-sectional study was carried out in the Department of Medicine, Rajshahi Medical College Hospital to evaluate the adverse effects of sodium stibogluconate in the treatment of visceral leishmaniasis. Out of 30 patients, 19 patients (63.33%) developed abnormalities in ECG. Among them 14 patients (46.67%) developed prolonged QTc, 6 patients (20%) developed Twave inversion and 1 patient (3.33%) developed transient first degree heart block. No patient developed symptomatic arrhythmia. Five patients (16.67%) developed transient raise of bilirubin, 11 patients (36.67%) developed raised SGPT. None of them developed clinical hepatitis. Twenty three patients (76.67%) developed raised serum amylase but none developed clinical pancreatitis. There was no change in renal function. No adverse effects were noted on complete blood count. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13659 KYAMC Journal Vol. 3, No.-1, June 2012 pp.239-243